191k views
5 votes
Click an item in the list or group of pictures at the bottom of the problem and, holding the button down, drag it into the correct position in the answer box. Release your mouse button when the item is place. If you change your mind, drag the item to the trashcan. Click the trashcan to clear all your answers.

Solve each equation.

(2x - 1)(3x + 2) = x + 292

User Kmaschta
by
5.1k points

1 Answer

4 votes

Answer:

x = 7, -7

Explanation:

(2x-1)(3x+2)+x+292

3x - 2x +x = 2 - 1 + 292

(6)x - 294 = 6(x - 49)

Use communicative property of multiplication

Example: (A+B)(A-B)


Ax^(2) -AB+BA-Bx^(2) =Ax^(2) -AB+AB-Bx^(2) =\\Ax^(2) -Bx^(2)

49 is the square of 7

x square is the square of x to the power of 1

(x+7)(x-7)

User Agradl
by
5.5k points